(untitled) (Semiárida, 2022)
Agricultural production requires the management of a set of physical, biological and economic systems. The uncertainty associated with these systems contributes to the complexity of the decision-making process and affects the efficiency of management. Agrometeorology is a discipline that unites meteorology and agricultural production and attempts to detect and define effects in order to later apply the knowledge obtained. have from the atmosphere to the practical aspects of said production. The relevance of atmospheric phenomena on agricultural production is evident when we think of catastrophes such as droughts, frosts, hailstorms or floods, but without reaching these extremes, more subtle variations in rainfall, solar radiation, temperature, wind or air humidity, have a considerable impact on the growth and development of plants (crops, weeds), animals and pests in general. Knowledge of the climate of a place and its variability, from records historical enough long, are essential for the agricultural producer to take the best of decisions, otherwise these would have a very random component. Climate is defined as the average state of the atmosphere and its variations, and it is possible to describe it through the behavior of the elements that compose it. Characterizing the climate of a place is important not only for agricultural planning but also for the correct interpretation of weather forecasts and trends. One of these tools to characterize the climate is climate statistics, which the authors of this publication make available to researchers, teachers, students, and advisors, so that they can be considered for the development of diagnoses, predictions and strategic designs in modern agronomy.